The versatile defender: exploring the multifaceted role of p62 in intracellular bacterial infection - Zhou, Yuhao; Hua, Shucheng; Song, Lei (Frontiers in Cellular and Infection Microbiology, 2023)
As a highly conserved, multifunctional protein with multiple domains, p62/SQSTM1 plays a crucial role in several essential cellular activities, particularly selective autophagy. Recent research has shown that p62 is crucial in eradicating intracellular bacteria by xenophagy, a selective autophagic process that identifies and eliminates such microorganisms. This review highlights the various roles of p62 in intracellular bacterial infections, including both direct and indirect, antibacterial and infection-promoting aspects, and xenophagy-dependent and independent functions, as documented in published literature. Additionally, the potential applications of synthetic drugs targeting the p62-mediated xenophagy mechanism and unresolved questions about p62’s roles in bacterial infections are also discussed.